2010
DOI: 10.2334/josnusd.52.411
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound, color Doppler imaging and radiography to monitor periapical healing after endodontic surgery

Abstract: This study evaluated the effectiveness of ultrasound, color Doppler imaging and conventional radiography in monitoring the post-surgical healing of periapical lesions of endodontic origin. Fifteen patients who underwent periapical surgery for endodontic pathology were randomly selected. In all patients, periapical lesions were evaluated preoperatively using ultrasound, color Doppler imaging and conventional radiography, to analyze characteristics such as size, shape and dimensions. On radiographic evaluation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 24 publications
4
25
0
4
Order By: Relevance
“…27 (2) so it promotes the reparative process of bone defect. As per expected no local reaction was seen during first two weeks in both groups but sonographically sprouting small blood vessels network at end of two weeks in Group II, as reported by Williamson et al 9 Hamanishi et al 10 and Tikku et al 11 With radiographic findings of intercortical callus formation within 60 days were good indication for local reaction of cancellous bone scaffold coated with nano-HA to act as stimulator to provide suitable bed for blood vessels penetration as compared to Group I. The status of bone, the vascularity, callus formation and viability of bone is a very important factor, in assessing the successful outcome of various surgical procedures.…”
Section: Value Of Color Doppler Ultrasonography and Radiography For Tsupporting
confidence: 60%
“…27 (2) so it promotes the reparative process of bone defect. As per expected no local reaction was seen during first two weeks in both groups but sonographically sprouting small blood vessels network at end of two weeks in Group II, as reported by Williamson et al 9 Hamanishi et al 10 and Tikku et al 11 With radiographic findings of intercortical callus formation within 60 days were good indication for local reaction of cancellous bone scaffold coated with nano-HA to act as stimulator to provide suitable bed for blood vessels penetration as compared to Group I. The status of bone, the vascularity, callus formation and viability of bone is a very important factor, in assessing the successful outcome of various surgical procedures.…”
Section: Value Of Color Doppler Ultrasonography and Radiography For Tsupporting
confidence: 60%
“…Gundappa et al [22] reported that US demonstrated a high diagnostic accuracy in the differentiation of periapical gran- ulomas and radicular cysts with a side-by-side comparison between US and hisopathology. Recent studies suggest that the Doppler imaging could be promising technique for monitoring the healing of periapical lesions [23][24][25].…”
Section: Periapical Lesionsmentioning
confidence: 99%
“…2 Son zamanlarda modern diĢ hekimliği radyolojisi BT, MRG, Sintigrafi ve USG gibi birçok ileri görüntüleme tekniklerini kullanmaktadır. 3 DiĢ Hekimliğinde USG maxillofasial bölge fraktürlerinin saptanmasında 4 , servikal lenfadenopatinin değerlen-dirilmesinde 5 , baĢ ve boyun bölgesindeki çeĢitli yumuĢak doku kitlelerinin incelenmesinde 5 , çiğneme ve boyun kaslarının değerlendirilmesinde 6,7 , Temporomandibular eklemin incelenmesinde 8 , periapikal lezyonların değerlendirilmesinde 9,10 ve tükürük bezlerinin incelenmesinde kullanılmaktadır ve daha birçok alanda Bazı hastaların dental muayeneleri için alınan panoramik radyografilerde fokal through içerisinde yer alan kalsfikasyonlar görülebilir. Fakat bu görüntüler iki boyutlu olduğu için bu yapıların tam olarak lokalizasyonları yapılamaz.…”
Section: Tartişma Ve Sonuçunclassified